Diagnostic performance of a streamlined 18F-choline PET-CT protocol for the detection of prostate carcinoma recurrence in combination with appropriate-use criteria. Issue 7 (July 2018) - Frood, R.; Baren, J.; McDermott, G.; Bottomley, D.; Patel, C.; Scarsbrook, A.
Abstract : Aim: To evaluate the efficacy of single time-point half-body (skull base to thighs) fluorine-18 choline positron emission tomography-computed tomography (PET-CT) compared to a triple-phase acquisition protocol in the detection of prostate carcinoma recurrence. Materials and methods: Consecutive choline PET-CT studies performed at a single tertiary referral centre in patients with biochemical recurrence of prostate carcinoma between September 2012 and March 2017 were reviewed retrospectively. The indication for the study, imaging protocol used, imaging findings, whether management was influenced by the PET-CT, and subsequent patient outcome were recorded. Results: Ninety-one examinations were performed during the study period; 42 were carried out using a triple-phase protocol (dynamic pelvic imaging for 20 minutes after tracer injection, half-body acquisition at 60 minutes and delayed pelvic scan at 90 minutes) between 2012 and August 2015. Subsequently following interim review of diagnostic performance, a streamlined protocol and appropriate-use criteria were introduced. Forty-nine examinations were carried out using the single-phase protocol between 2015 and 2017. Twenty-nine (69%) of the triple-phase studies were positive for recurrence compared to 38 (78%) of the single-phase studies. Only one patient who had a single-phase study would have benefited from a dynamic acquisition, they have required no further treatment or imaging and are currently under prostate-specific antigen (PSA) surveillance. Conclusion: Choline PET-CT remains a useful tool for the detection of prostate recurrence when used in combination with appropriate-use criteria. Removal of dynamic and delayed acquisition phases reduces study time without adversely affecting accuracy. Benefits include shorter imaging time which improves patient comfort, reduced cost, and improved scanner efficiency. Highlights: Choline PET/CT remains a useful tool for the detection of prostate cancer recurrence. The sensitivity of choline PET/CT to detect recurrence can be improved by using appropriate criteria. Removal of dynamic and delayed acquisition phases reduces study time without adversely affecting accuracy.